Keanekaragaman Jenis Burung Dilindungi pada Kawasan Cagar Alam Mutis Timau Provinsi Nusa Tenggara Timur - Adityo Umbu Djaga Ladu Tanggu; Maria M. E. Purnama; Norman P. L. B. Riwu Kaho; Muhamad Soimin (Wana Lestari, 2024)
Birds are one component of the ecosystem that has an important role. Because ecologically, birds have a role in spreading seeds, helping pollinate plants and as a bio-indicator or supporting component for environmental quality. This research aims to find out the types of birds that are included in the list of protected bird species based on LHK regulation No.P.106/2018. The method used in this research is a combination of the point count method and the transect method. Data analysis in this research uses Shannon-Wiener analysis, namely to calculate species diversity. The results of the research show that of the 63 bird species found, 7 bird species are included in the list of protected species based on LHK regulation No.P.106/2018 and based on the IUCN conservation status, the bird species diversity index is classified as high. The calculation results show the value (H'=3.498). As time goes by, the diversity of bird species in the Mutis Timau Nature Reserve area will decrease or increase according to the adaptability of birds to changes in habitat conditions due to significant climate change or competition with other wild animals.